The effect of healthcare industry growth on the interest rate: Economic growth of selected ASEAN country - Nina Khairinai, Zailain; Intan Maizura, Abd Rashid; Buthiena, Kharabsheh; Wan Ahmad Fauzi, Wan Husain; Irza Hanie, Abu Samah; Hariri, Hamzah (AIP Publishing, 2023)
The objective of the study was to analyze the consequences of interest rate on healthcare industry in selected ASEAN country for the period 2005 to 2015. Interest rate were established as the dependent variable while the independent variables were economic growth, inflation, unemployment rate, exchange rate and healthcare industry. The study sought to understand the relationship between the independent variables and dependent variable. This research will be focused on healthcare industry in five selected Asian country which is Malaysia, Singapore, Vietnam, Indonesia and Thailand because nowadays healthcare industry seem to be an important part in the economy of a country. The sample of countries selected are depended on their interest rate performance. While, the data provided in this research are based on World Bank data covers the period from 2005 to 2015. In addition, the researcher proposed to use the dynamic panel data in order to explore the relationship between interest rate and a number of independent variables: economic growth, inflation, unemployment, exchange rate and healthcare industry. These independent variable are choose as they seen to be the most key factor that affecting interest rate. Furthermore, the researcher decide to use healthcare expenditure as new measurement for this study.